Barriers and facilitators to older adults acceptance of camera-based active and assisted living technologies: a scoping review protocol - Dinsmore, John (My University, 2023)
Objective: To identify and synthesize evidence on the barriers and facilitators to older adults’ acceptance of camera-based active and assisted living (AAL) technologies in the home. Introduction: Camera-based AAL technologies have been heralded as an important solution to population ageing. By leveraging state-of-the-art computer vision techniques, camera-based AAL technologies can secure greater levels of safety, health, and independence for older adults whilst benefiting their desires to age-in-place. However, these technologies face widespread rejection and are at present scarcely used. A critical first step toward enhancing older adults’ acceptance and uptake of camera-based AAL technologies is to understand the barriers and facilitators to their acceptance of said technology. Inclusion criteria: This review will consider primary studies reporting data on the barriers and facilitators to the acceptance of camera-based AAL technologies among community-dwelling older adults aged 60 and above. No date or language restrictions will be applied. Methods: Following JBI scoping review methodology, key electronic databases ( e.g., MEDLINE, CINAHL, Embase, Web of Science, ACM Digital Library, IEEE Xplore) and the grey literature (e.g., Google Scholar) will be searched to locate both unpublished and published articles of relevance. Retrieved citations will undergo independent screening against pre-defined eligibility criteria. Data will be independently extracted and mapped to the Theoretical Domains Framework with guidance from a pre-piloted coding manual. Results will be presented in tabular form accompanied by a narrative summary of barriers and facilitators.
Epidemiology & Community Health
SSM Annual Scientific Meeting
Keywords: ambient assisted living, active and assisted living, computer vision, technology acceptance, older adults; Ageing; Chronic Illness; Chronic Illness self-management; Digital Health; Health psychology; Age-related disability; Chronic Health Condition; Health